Serum Albumin Binding Inhibits Nuclear Uptake of Luminescent Metal‐Complex‐Based DNA Imaging Probes. Issue 33 (1st July 2015) - Wragg, Ashley; Gill, Martin R.; McKenzie, Luke; Glover, Caroline; Mowll, Rachel; Weinstein, Julia A.; Su, Xiaodi; Smythe, Carl; Thomas, Jim A.
Abstract The DNA binding and cellular localization properties of a new luminescent heterobimetallic IrIIIRuII tetrapyridophenazine complex are reported. Surprisingly, in standard cell media, in which its tetracationic, isostructural RuIIRuII analogue is localized in the nucleus, the new tricationic complex is poorly taken up by live cells and demonstrates no nuclear staining. Consequent cell‐free studies reveal that the IrIIIRuII complex binds bovine serum albumin, BSA, in Sudlow's Site I with a similar increase in emission and binding affinity to that observed with DNA. Contrastingly, in serum‐free conditions the complex is rapidly internalized by live cells, where it localizes in cell nuclei and functions as a DNA imaging agent. The absence of serum proteins also greatly alters the cytotoxicity of the complex, where high levels of oncosis/necrosis are observed due to this enhanced uptake. This suggests that simply increasing the lipophilicity of a DNA imaging probe to enhance cellular uptake can be counterproductive as, due to increased binding to serum albumin protein, this strategy can actually disrupt nuclear targeting.